EVALUATION OF BREASTFEEDING PRACTICES IN THE COMMUNITY ATTENDING A TERTIARY CARE HOSPITAL - Dr. Asim Ikram; Dr. Aisha Sajid (Journal of University Medical & Dental College, 1970)
ABSTRACT Objectives: To evaluate the breastfeeding practices in the community. Methods: This was an Out Patient Department (OPD) based cross sectional study conducted at pediatrics department of Madina Teaching Hospital, Sargodha Road, Faisalabad, in 4 months period starting from September 2009 to December 2009. Four hundred women attending the pediatric OPD having children between one to five years of age were included. A questionnaire was prepared regarding the breastfeeding practices. The data was analyzed statistically by using SPSS version 17 using chi-square as test of statistics. P-value <0.05 was considered significant. Results: Total 400 mothers of children were interviewed, minimum age of child was 12 months, and maximum age was 60 months with mean age of 33 months (SD 13.4). Minimum maternal age was 18 years; maximum age was 45 years with mean age of 29 years (SD 5.3). Most of the mothers belonged to lower socioeconomic status, had low literacy status, and were housewives. Breastfeeding initiated in 90% of cases, but exclusive breastfeeding till 6 months was given only in 23% of cases (p= 0.055). About 51% of women included in the study started topfeeding their children before 6 months of age. Many mothers believe in giving breastfeed on 3rd day. Topfeeding was diluted cows milk and insufficient milk production was the most common cause of cessation of breastfeeding. Conclusion: The risk factors need to be determined that lead to inadequate breastfeeding practices in the community in order to improve the nutritional status of infants in Pakistan.